Itu Pengaruh Bauran Promosi Terhadap Minat Beli (Survei Konsumen Produk Susu Vidoran Di Borma Wilayah Cimahi) - Irma Susanti; Prihartono (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to evaluate the influence of promotional mix on consumer purchasing interest in Susu Vidoran products in the Borma area of Cimahi. Focusing on variables such as advertising, sales promotion, public relations, and direct marketing, it provides insights to marketers on the effectiveness of current promotion strategies. The research focuses on Susu Vidoran consumers in Borma, Cimahi, with an estimated population of 150 that came to store for 3 month. Sampling used the Slovin formula, with a 10% error rate and population of 150. As a result, 60 respondents were sampled for adequate representation. Based on simple linear regression analysis, the study shows that the promotional mix significantly influences consumer purchasing interest. The promotional mix variables explain about 30.2% of the variation in purchasing interest, with 69.8% influenced by other factors not discussed. These findings offer clearer insights for marketers in designing more effective promotion strategies and contribute significantly to marketing literature, particularly in the context of dairy products. Thus, effective promotion strategies can enhance purchasing interest and sales of Susu Vidoran products in competitive markets.